(untitled) - Coulthard, Glen J. (New York, 2014)
Microsoft Office 2013: ProjectLearn is a new text with a project-based approach to engage students learning Microsoft Office 2013. The approach allows students to focus on the end result and complete the tutorial for each Office application with quality "artifacts" - projects that help students develop a portfolio they can display in their careers. The structured series has two projects per chapter. Additional lessons provide a consistent framework for learning with a lesson overview, skills preview, and project practice. At the end of each chapter are two "on your own" projects that each have three "work it out" exercises. By working directly within the project experience, students develop a deeper understanding of how skills essential to their future careers.
Keywords: Business,Kinh doanh; Computer programs,Chương trình máy tính